Konstruksi Skala Kepedulian terhadap Penggunaan Energi - Rizal Kurniawan; Saifuddin Azwar (Jurnal Ilmu Perilaku, 2017)
Using electricity and fuel oil might have some negative impact towards the national economy and the environment. Psychological scale for measuring awareness of energy usage has never been tested before. The main purpose of this study is to construct psychological scale for measuring energy usage. The concept of Amburgey (2012) has been used to describe of psychological concern that are perceived threat and desired change. Perceived threat is an evaluation of a person to a problem and desired change is one’s willingness to resolve that problem. Four hundred-thirty eight students were enrolled in this study with a mean of age 21 years old. The results of content item validation show that one item from perceived threat’s subscale has value of Aiken (V) less than .50 and all of items from desired change’s subscale have V value greater than .50. Result from item’s discrimination process show that 40% items from perceived threat’s subscale has low of discrimination power and desired change’s sub scale has 31%. Alpha value for perceived threat’s subscales is .76 and desired change’s sub scale is .78. The concern for energy usage scale has poor model fit.